НЕКОТОРЫЕ ВОПРОСЫ СТАНОВЛЕНИЯ КОНСУЛЬСКОЙ СЛУЖБЫ В КАЗАХСТАНЕ И РОССИИ (Journal of actual problems of jurisprudence, 2019)
Thus, in this article the author examines the formation and development of the consular institution associated with thedevelopment of trade and merchant shipping, colonial interests, expanding markets. Economic and trade functions of consulatesgradually grew and socio-cultural, political.